Outpatient medical management of later second trimester abortion (18-23.6 weeks) with procedural evacuation backup: A large case series - Sruthi Chandrasekaran; Samantha Ruggiero; Gabrielle Goodrick (Elsevier, 2024)
Objective: Document the clinical outcomes of an outpatient medical management with procedural evacuation backup procedure for abortions between 18 weeks zero days to 23 weeks six days gestation. Study design: We conducted a retrospective medical records review of adult patients who received mifepristone and repeated misoprostol for second trimester abortion with procedural evacuation backup at an Arizona clinic between October 2017 and November 2021. We extracted patient demographics; pregnancy and medical history; and preoperative, intraoperative, and postoperative data. We assessed abortion outcomes, including procedure timing, mode of completion (medication alone or medications and procedural evacuation), and safety. Results: All 359 patients had a complete abortion with 63.5% of patients completing with medication alone and 36.5% with procedural evacuation backup. The median time from first dose of misoprostol to fetal expulsion was six hours, among those who completed the abortion with medications alone. Of those who received procedural evacuation as backup, the median time for procedural evacuation was 10 minutes. The vast majority of patients (99.4%) did not have any adverse events. Two safety incidents (0.6%) occurred, a broad right ligament tear and a uterine rupture. Conclusion: Patients in one outpatient setting safely and effectively received medical management of second trimester abortion with procedural evacuation backup, and two thirds completed with medications alone. Implications: Outpatient settings may consider medical management of abortion between 18 and 24 weeks with procedural evacuation back-up as a safe, effective, and manageable second trimester abortion option. Additional research is needed on patient experience and satisfaction.